Perancangan Sistem Informasi Akreditasi Dengan Metode Rapid Application Develpoment (RAD) - Sobri, Muhamad; Akbar, Yunata Kandhias (FORMAT, 2024)
Accreditation serves in order to guarantee the quality of study programs and Higher Education externally to protect student and public interest, also to determine feasibility of study programs and Higher Education based on criteria that refer to national standards of Higher Education. However, the implementation of accreditation in Mercubuana University currently is still using manual process from the preparation, arrangement, monitoring, and vitalization process as well. Therefore, this thesis will propose the accreditation system which is expected to be able to provide ease of use in terms of time efficiency and effectiveness for all elements such as: Rector, vice rector, deans, vice deans, heads of program, vice heads of program, and lecturers in designing study program accreditation as well as Higher education accreditation. This system was created by using RAD (Rapid Application Development) model with stages of business modelling, data modelling, process modelling, application creating, assessing, and replacing. This system also created by using UML (Unified Modelling language) method with details of use case diagram, activity diagram, sequence diagram, and class diagram. The test results from the process that has been tested by using the black box method can be concluded that the system is running well and as expected.